1998
DOI: 10.1046/j.1523-1755.1998.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma α2 macroglobulin is increased in nephrotic patients as a result of increased synthesis alone

Abstract: Increased plasma alpha 2M concentration in nephrotic patients is therefore a result of increased synthesis alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Expression of A2M mRNA is unique to the chicken oviduct. In humans, A2M is synthesized primarily in the liver [43,44] and as a major plasma protein, it makes up roughly 8-10% of the total protein in human blood [45,46]. However, in chickens, A2M (also known as ovomacroglobulin or ovostatin) is synthesized in the oviduct and found in egg whites [14,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of A2M mRNA is unique to the chicken oviduct. In humans, A2M is synthesized primarily in the liver [43,44] and as a major plasma protein, it makes up roughly 8-10% of the total protein in human blood [45,46]. However, in chickens, A2M (also known as ovomacroglobulin or ovostatin) is synthesized in the oviduct and found in egg whites [14,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Our immunohistochemical findings showed that both groups of AD-treated rats had higher immunostaining for angiotensin II, endothelin and TGF-β in the tubular cells from the renal cortex. Several lines of evidence support a role for angiotensin II and endothelin in the progression of renal disease [11, 19, 45, 46, 47]. The presence of angiotensin II in the cytoplasm of tubular cells from these animals suggests an increase in ultrafiltration and reabsorption of this polypeptide, which has been reported to stimulate TGF-β production [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the effect of peritoneal dialysis on serum CETP are lacking. Hepatic expression and serum concentration of CETP are elevated in patients with heavy proteinuria [36,37]. Given the significant losses of proteins with peritoneal dialysis procedure, we speculate that serum CETP may be elevated in patients undergoing peritoneal dialysis.…”
Section: Hdl Metabolism and Function In Ckdmentioning
confidence: 99%